On the harm of badger hole in embankments and its control measures - Shen Chong; Li Yue; Zhang Hua (E3S Web of Conferences)
Embankments have an important impact on the safe operation of river projects, the stability of surrounding towns and the safety of people’s lives and property. This paper expounds the formation reason of badger hole and deeply analyzes the harm of badger hole to the embankment, and discusses the past treatment measures and improved grouting treatment method of the badger cave in combination with the governance situation of Gucheng River Bureau (hereinafter referred to as the “Gucheng Bureau”), aiming to provide reliable theoretical and practical references for ensuring the safety and stability of the embankments.